Pengaruh Variasi Konsentrasi Natrium Hidroksida (NaOH) Terhadap Sifat Fisik Sabun Padat Berbahan Minyak Goreng Bekas Pakai - Mikhania Christiningtyas; Nur; Risky Ayu Paramita, Denok; Patihul; Riskha Nurmalasari, Dewi (JURNAL FARMASI GALENIKA, 2025)
Soap is a cleanser made by a chemical reaction between sodium or potassium and fatty acids from vegetable oils or animal fats. Used cooking oil can be used as the main ingredient for the oil component in making solid soap used for washing dishes. This research aims to determine the effect of variations in NaOH concentration on the physical properties of solid soap preparations made from used cooking oil. Preparations were made with NaOH concentrations between 5% (F1), 8.5% (F2) and 12% (F3). The physical property tests carried out are organoleptic tests including texture, color and odor, pH test, water content test and foam height test. Organoleptic data shows that F1 has a smooth texture, yellow color and a weak lemon smell. F2 has a slightly rough texture, yellow color and a weak lemon smell. F3 has a rough texture, yellow color and does not smell like lemon. F1 pH value is 10.36 ± 0.16; F2 was 10.52 ± 0.33; and F3 of 10.47 ± 0.18. The results of the water content test showed that F1 data was 0.91% ± 0.25; F2 was 0.88% ± 0.04; and F3 of 1.04% ± 0.20. The foam height test results showed that F1 data was 6.97 ± 1.00 cm, F2 was 6.57 ± 0.38 cm, and F3 was 5.83 ± 0.32 cm. The conclusion is that NaOH variations concentration have an effect on the texture and smell of soap but have no effect on color, pH, water content and height of soap foam.